Bio-Oil Hydrotreatment for Enhancing Solubility in Biodiesel and the Oxydation Stability of Resulting Blends - Botella, Lucía; Stankovikj, Filip; Sánchez, José L.; Gonzalo, Alberto; Arauzo, Jesús; Garcia-Pérez, Manuel (Frontiers in Chemistry, 2018)
The major challenge for the pyrolytic conversion of lignocellulosic materials into crude bio-oil is the poor quality of the final product. Several strategies (addition of solvents, production of emulsions, and extraction with biodiesel) have been studied to improve its fuel properties. The extraction with biodiesel is an interesting solution because it allows direct utilization of some bio-oil fractions as fuels. However, fraction extracted with biodiesel is typically between 10 and 18 wt. %. In this paper we studied mild hydrotreatment of pyrolysis oil to enhance its solubility in biodiesel. The study was conducted with BTG and Amaron oils hydrotreated at temperatures between 200 and 325 °C in the presence of Ru/C catalyst. Hydrotreated oils generated three phases: top oil (light hydrocarbons), middle aqueous phase and bottom heavy oil phase. Each of the phases was characterized and the content of acetic acid, phenols, aromatic compounds and linear alkane hydrocarbons quantified. The upgraded bio-oils were more soluble in biodiesel than the crude bio-oils, obtaining blends with up to 48 and 38 wt. % for the BTG and Amaron bio-oil, respectively. Some of the fuel properties of the resulting blends are also reported here.